Method for removing impurities in glass strengthening salt bath

By adding additives of specific composition to the glass strengthening salt bath, the problem of salt bath contamination caused by iron ions and lithium ions is solved, the clean recovery of the salt bath and the reduction of production costs are achieved, ensuring the stability and efficiency of the glass strengthening process.

CN120774649APending Publication Date: 2025-10-14CHANGSHU JIAHE DISPLAY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410398825.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

In the existing technology, the increase in the concentration of iron ions and lithium ions in the glass strengthening salt bath leads to surface defects and unstable product quality. The traditional method is costly and inefficient, and the trisodium phosphate additive easily causes uneven spots on the glass surface and turbidity in the molten salt.

Method used

An additive consisting of 20-60% SiO2, 10%-40% Al2O3, 20-50% of a first metal oxide and 0-30% of other oxides is used to remove iron ions and lithium ions from a glass strengthening salt bath by reacting at 460-550°C for 3-20 hours. The additive is in the form of particles, flakes or porous particles and is prepared by smelting and water quenching or rolling.

Benefits of technology

It effectively removes iron and lithium ions from the salt bath, reduces surface defects, lowers production costs, and improves production efficiency. The additives can be reused to ensure the stability and quality of the glass strengthening process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120774649A_ABST
    Figure CN120774649A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing impurities in a glass strengthening salt bath, which comprises the following steps: preparing an additive from 20-60% by mass of SiO2, 10-40% by mass of Al2O3, 20-50% by mass of a first metal oxide and 0-30% by mass of other oxides, weighing the additive accounting for 1-2% of the mass of the glass strengthening salt to be removed, adding the additive into the glass strengthening salt to be removed, and reacting at 460-500 DEG C for 3-20 hours to obtain the impurities in the glass strengthening salt bath. The iron ions in the glass strengthening salt bath are removed. According to the method, Fe ions brought by the strengthening furnace and the sample holder in the salt bath can be effectively removed, so that the salt bath is recovered to be clean, and poor appearance caused by multiple concave and convex points is reduced. The problem that in the prior art, after salt bath pollution, a new salt bath material needs to be replaced is solved, and the production efficiency is improved; meanwhile, new salt bath materials are prevented from being input, and the production cost is reduced. And the additive can be quickly and conveniently taken out, so that the influence on the production efficiency is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of processing technology of glass-ceramics, and particularly relates to an additive for salt bath impurity removal in glass strengthening, a preparation method and application thereof. BACKGROUND

[0002] Ion exchange strengthening technology is a common means for modifying glass. The principle of ion exchange technology is to place the glass in a molten salt, so that the network external ions in the glass and the monovalent metal ions in the salt bath can mutually diffuse, so that the glass appears a composition gradient. Ion exchange technology can make the glass appear stress and refractive index gradient from the surface to the interior, and is commonly used for the preparation of chemically tempered glass and gradient refractive index materials.

[0003] The monovalent metal element salt used for ion exchange includes lithium salt, sodium salt, potassium salt, and mixed salt thereof.

[0004] On the one hand, in the production process of chemically strengthened glass cover plate, the strengthening furnace and the sample holder used for furnace feeding are both iron products. During long-term use, they are exposed to air and can rust, which causes the content of Fe ions in the strengthening furnace water to increase with the increase of the number of uses and the use time. The salt used in the production of chemical strengthening is mainly nitrate, and the decomposition temperature of ferric nitrate is relatively low, which can easily decompose to generate iron oxide precipitate. The precipitate can cause defects such as concave-convex points on the appearance of the glass material. In addition, in the glass processing plant, the salt bath furnace is generally 8 tons or even higher, and the number of glass sheets treated in one strengthening process is as high as tens of thousands. In such a large-scale ion exchange environment, if the salt bath is not environmentally controlled, the strengthened glass is prone to surface defects, the strength of the glass between batches decreases significantly, and the salt bath is gradually disabled.

[0005] On the other hand, in the chemical strengthening process, lithium ions existing in the glass exchange with sodium ions and potassium ions in the molten salt (diffusion from high concentration to low concentration) after high-temperature salt bath, causing the concentration of lithium ions in the molten salt to increase. Although the concentration change of lithium ions is only ppm level, the concentration has a significant impact on the stress, strength and outer dimensions of the glass after chemical strengthening, resulting in difficulty in effectively controlling the product quality due to the fluctuation of lithium ion concentration. This situation is commonly referred to as salt bath poisoning in the field. To solve this problem, the conventional method is to replace the new molten salt, but this solution is costly and time-consuming, and seriously wastes production resources. At present, the industry usually adds TSP (trisodium phosphate) to reduce the lithium ions in the molten salt, but this solution has the following problems: insoluble phosphate generated by the reaction of trisodium phosphate added to the molten salt is easy to adhere to the surface of the glass, causing concave and convex points to appear on the surface of the glass in the subsequent process, and too many phosphate ions in the molten salt can easily corrode the glass, resulting in product scrap. Moreover, as the amount of addition increases, the increase of insoluble substances in the molten salt makes the molten salt turbid and difficult to clarify, affecting the production efficiency.

[0006] Therefore, it is necessary to provide a material for purifying deteriorated or impure salt compounds containing impurities such as iron or lithium ions, to improve production efficiency, reduce production cost, greatly reduce the use amount of potassium nitrate and sodium nitrate, and ensure the stability and strength of batch production of strengthened glass, which is environmentally friendly and pollution-free. SUMMARY

[0007] In view of the above problems in the prior art, the present application aims to provide an additive for removing impurities from a glass strengthening salt bath, a preparation method and application thereof. The technical solution of the present application is as follows: The first technical solution of the present application is a method for removing impurities from a glass strengthening salt bath, which comprises the following components in mass percentage: 20-60% SiO2, 10%-40% Al2O3, 20-50% first metal oxide and 0-30% other oxides to form an additive. The additive is weighed at 1-2% of the mass of the glass strengthening salt to be removed, and then added to the glass strengthening salt to be removed. The mixture is reacted at 460-500 DEG C for 3-20 hours to remove iron ions in the glass strengthening salt bath.

[0008] The first metal oxide is one or more of Li2O, Na2O, K2O, R b2 O, and the other oxides are one or more of P2O5, CaO, MgO, BaO, SrO, AgO, ZrO2, Sb2O3, ZnO, B2O3, Fe2O3, NiO and TiO2.

[0009] The additive is in the form of granules or flakes or porous. When the additive is in the form of granules, the average size is 1-20mm; when the additive is in the form of flakes, the thickness is 0.3-1.2mm; when the additive is in the form of porous, the average pore size is 1-10mm.

[0010] The preparation method of the additive is: 20-60wt% SiO2, 10-40wt% Al2O3, 20-50wt% alkali metal oxide and 0-30wt% other oxides are mixed, the mixture is smelted at 900-1600℃ to form a liquid state, and then granules, flakes or porous are prepared. Further, the liquid state mixture is granulated by water quenching, the water quenching temperature is 5-85℃; the liquid state mixture is prepared into flakes by calendering or drawing; the liquid state mixture is made into porous by adding a foaming agent, the foaming agent is carbon powder or / and sodium carbonate.

[0011] The second technical solution of the present application is: a method for removing impurities in glass strengthening salt bath, characterized in that: the additive is made of 30-55% SiO2, 5%-30% Al2O3, 35-55% first metal oxide and 1-6% other oxides, 1-2% of the additive is weighed according to the mass of the glass strengthening salt to be removed, and is added to the glass strengthening salt to be removed, and lithium ions in the glass strengthening salt bath are removed at 450-550℃ for 4-16h.

[0012] The third solution provided by the present application is: an additive for removing impurities in glass strengthening salt bath, which is composed of 20-60% SiO2, 10%-40% Al2O3, 20-50% first metal oxide and 0-30% other oxides by mass. Preferably, 30-50wt% SiO2, 15-30wt% Al2O3, 30-50wt% first metal oxide.

[0013] Further, the first metal oxide is one or more of Li2O, Na2O, K2O, R b2 O, one or more of P2O5, CaO, MgO, BaO, SrO, AgO, ZrO2, Sb2O3, ZnO, B2O3, Fe2O3, NiO, TiO2.

[0014] Further, the additive is in the form of granules or flakes or porous.

[0015] Furthermore, when the additive is in the form of particles, its average size is 1-20 mm; when the additive is in the form of flakes, its thickness is 0.3-1.2 mm; when the additive is in the form of porous particles, its average pore size is 1-10 mm.

[0016] A method for preparing the above-mentioned additive for removing impurities in a glass strengthening salt bath comprises the following steps: thoroughly mixing 20-60wt% SiO2, 10-40wt% Al2O3, 20-50wt% alkali metal oxides and 0-30wt% other oxides, melting the mixture at 900°C to 1600°C to form a liquid, and then forming the mixture into granular, flake or porous forms.

[0017] Furthermore, the liquid mixture is made into particles by water quenching, and the water quenching temperature is 5-85°C.

[0018] The liquid mixture is prepared into a sheet by calendaring or drawing.

[0019] The liquid mixture is made porous by adding a foaming agent, wherein the foaming agent is carbon powder and / or sodium carbonate and others.

[0020] A method for applying the aforementioned additive for removing impurities in a glass strengthening salt bath comprises weighing 1-2% of the mass of the glass strengthening salt to be removed, adding the additive to the glass strengthening salt to be removed, and reacting at 460-500° C. for 3-20 hours.

[0021] A fourth technical solution provided by the present invention is an additive for removing impurities from a glass strengthening salt bath, comprising, by weight, 30-55% SiO2, 5-30% Al2O3, 35-55% a first metal oxide, and 1-6% other oxides. Preferably, the composition comprises 35-45% SiO2, 18-27% Al2O3, 33-48% the first metal oxide, and 2-5% other oxides.

[0022] Furthermore, the first metal oxide is one or two of Li2O, Na2O, and K2O; the other oxide is one of P2O5 or MgO, preferably P2O5.

[0023] Furthermore, the additive is in the form of particles or flakes.

[0024] Furthermore, when the additive is in the form of particles, the average size thereof is 2-10 mm; when the additive is in the form of flakes, the area of ​​the flakes is 25 mm. 2 -900mm 2 , and has a thickness of t=0.2-0.8mm.

[0025] Preferably, the sheet shape is adopted, and the thickness is 0.3-0.6mm, with an area of 100mm 2 -600mm 2 .

[0026] A preparation method of the additive for glass strengthening salt bath impurity removal, comprising the following steps: Step 1: 30-55wt% SiO2, 5-30wt% Al2O3, 35-55wt% first metal oxide and 1-6wt% other oxides are mixed thoroughly: Step 2: the additive raw materials are preheated; preferably, the preheating temperature is 300-400℃; Step 3: the additive in step 2 is mixed and smelted to obtain a granular or sheet-shaped additive.

[0027] Further, the smelted glass liquid is made into particles by water quenching, and the water quenching temperature is 5-85℃.

[0028] The smelted glass liquid is rolled into a sheet shape by a pressure roller.

[0029] An application method of the additive for glass strengthening salt bath impurity removal, weighing 1-2% of the additive to be removed of the glass strengthening salt to be removed, and adding the additive to the glass strengthening salt to be removed, under the condition of 450-550℃, and the reaction time is 4-16h. The glass strengthening salt is a mixture or single fused salt of potassium nitrate, sodium nitrate and lithium nitrate.

[0030] The present application provides an additive for glass strengthening salt bath impurity removal, which can effectively reduce the concentration of Fe ions in the molten salt. The additive is mainly amorphous before being put into the furnace, and reacts with Fe in the furnace water after being used in the furnace to generate sodium aluminum silicate crystals or other crystals, thereby achieving the effect of removing iron ions in the glass strengthening salt bath. It is speculated that the principle of the iron removal agent is that the alkali metal in the additive and the Fe in the furnace water undergo ion exchange; on the other hand, the additive of the present application can effectively absorb and control the concentration of lithium ions, and the use state of the additive can be quickly confirmed according to the appearance, thereby saving the additive and reducing the production cost The additive of the present application can effectively remove the Fe ions in the salt bath caused by the strengthening furnace and the sample holder when the additive is added to the ion exchange chemical strengthening salt bath, so that the salt bath can be restored to clean, and the appearance defects caused by the many concave and convex points are reduced. The present application solves the problem that the salt bath material must be replaced after being contaminated in the prior art, avoids the replacement of the production efficiency; at the same time, the input of new salt bath material is also avoided, and the production cost is reduced. Moreover, the additive can be quickly and conveniently taken out, reducing the influence on the production efficiency, in addition, the salt bath purification additive material can be repeatedly used after being treated to release and absorb the impurity ions, greatly reducing the usage amount and the cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the XRD pattern of the additive prepared in Example 1 of the present invention; Figure 2 This is the XRD pattern of the additive prepared in Example 1 of the present invention after being put into the furnace and treated at 480° C. for 8 hours; Figure 3 This is the XRD pattern of the additive prepared in Example 1 of the present invention after being treated at 480° C. for 8 hours before being put into the furnace; Figure 4 This is an SEM photograph of the glass after salt bath strengthening treatment without removing iron ions according to Example 1 of the present invention; Figure 5 This is an SEM photograph of the glass after salt bath strengthening treatment without removing iron ions according to Example 1 of the present invention; Figure 6 This is the XRD pattern of the additive prepared in Example 7 of the present invention; Figure 7 This is the XRD pattern of the additive prepared in Example 7 of the present invention after being put into the furnace (completely used) and treated at 480° C. for 6 hours; Figure 8 This is the XRD pattern of the additive prepared in Example 7 of the present invention after being put into the furnace (not completely used) and treated at 480° C. for 6 hours. DETAILED DESCRIPTION

[0032] In order to make the technical problems to be solved by the present invention, the technical solutions and the beneficial effects more clear, the present invention is further described in detail below with reference to examples. It should be understood that the specific examples described herein are only used to explain the present invention and are not used to limit the present invention. Example

[0033] First, the additive was prepared and characterized. 36wt% SiO2, 26wt% Al2O3 and 38wt% Na2O were fully mixed, and the mixture was melted between 900℃ and 1600℃ to form a liquid state. The liquid mixture was quenched into particles by water. The water quenching temperature was 5-85℃ to obtain a granular additive with an average particle size of 1-20mm. The composition of the prepared additive was 36wt% SiO2, 26wt% Al2O3 and 38wt% Na2O. The XRD pattern of the prepared additive is shown as follows: Figure 1 As shown by Figure 1 It can be seen that the additive is amorphous at this time. XRF and ICP tests were performed on it, and the test results are shown in Tables 1 and 2. In the ICP test, Al and Na were diluted 10,000 times, and Fe was diluted 100 times.

[0034] Table 1 XRF results of the additive prepared in Example 1 before use Component Mass fraction (wt%) <![CDATA[Na2O]]> 38.1052 Al2O3 26.1187 SiO2 35.4601 Other 0.316 Table 2 ICP results of the additive prepared in Example 1 before use Element Al Na Fe Content (ppm) 67790 161800 / Next, the prepared additive was put into the furnace for use. Weigh 1.5wt% of the additive in the glass strengthening salt bath containing iron ions, add it to the glass strengthening salt bath containing iron ions, and react at 500℃ for 3-20 hours. XRF and ICP tests were performed on the used additive. During the ICP test, Al and Na were diluted 10,000 times, and Fe was diluted 100 times. The results are shown in Tables 3 and 4. XRD tests were performed on the additive that was put into the salt bath for 8 hours. The test results are shown in Tables 3 and 4. Figure 2 As shown by Figure 2 It can be seen that sodium aluminum silicate crystals begin to form in the additive after it is put into the furnace. At the same time, the unused additive is also treated in a muffle furnace at 480℃ for 8 hours and then XRD test is performed. The results are as follows Figure 3 As shown, it is the same as before the follow-up furnace was used, and no changes have occurred.

[0035] Table 3 XRF results of the additive prepared in Example 1 after 8 hours of use Component Mass fraction Na2O 37.0533 Al2O3 26.6083 SiO2 35.624 Fe2O3 0.4338 Other 0.2806 Table 4 ICP results of the additive prepared in Example 1 after 8 hours of use Element Al Fe Na Content (ppm) 68532 81 158900 As shown in Table 1-4, after the additives were put into the furnace, the iron in the strengthening salt bath was successfully adsorbed into the additives. SEM tests were conducted on the glass-ceramics after different salt bath treatments before and after the iron ions in the salt bath were removed. The test results are as follows: Figure 4 and Figure 5 As shown in the results, it can be seen that the removal of additives can effectively reduce the generation of concave and convex points on the surface of the microcrystalline glass and reduce the appearance defect rate.

[0036] Examples 2-6 The overall preparation method and application method are the same as those in Example 1. The differences are the composition of the raw materials, the form of the additive, the temperature in the furnace when it is put into use (to remove impurities), and the amount of input, etc., as shown in Tables 5 and 6.

[0037] Table 5 Raw material composition and morphology of Examples 1-6 Example SiO2 (wt%) Al203(wt%) First type of metal oxide (wt%) Other metal oxide (wt%) Shape Size (mm) Example 1 36 26 Na2O 38 / Granular 1-10 Example 2 31 29 K2O 40 / Flaky 30*30 Example 3 44 31 Na2O 24 P2O5 Flaky 30*30 Example 4 36 17 <![CDATA[Na2O+K2O 45]]> P2O5 + CaO 22 Granular 1-10 Example 5 32 21 Na20 + K20 44 MgO 3 Porous 1-10 Example 6 38 23 Na2O 37 ZnO 2 Granular 1-10 Table 6 Comparison of the effects of Examples 1-6 on removing iron ions from the glass strengthening salt bath Decontamination experiment 1 Decontamination experiment 2 Decontamination experiment 3 Decontamination experiment 4 Decontamination experiment 5 Decontamination experiment 6 Decontamination experiment 7 Decontamination experiment 8 Additive Example 1 Example 2 Example 1 Example 3 Example 4 Example 5 Example 6 Example 4 Iron ion concentration in the salt bath to be purified 50 ppm 50 ppm 50 ppm 50 ppm 50 ppm 50 ppm 50 ppm 50 ppm Temperature of the salt bath to be purified (°C) 480 480 500 480 500 460 480 460 Additive addition amount in the salt bath to be purified 1.5 wt% of the mass of the salt to be purified 1.5 wt% of the mass of the salt to be purified 1.5 wt% of the mass of the salt to be purified 1.5 wt% of the mass of the salt to be purified 1.5 wt% of the mass of the salt to be purified 1.5 wt% of the mass of the salt to be purified 1.5 wt% of the mass of the salt to be purified 1.5 wt% of the mass of the salt to be purified Iron ion purification efficiency per 1 wt% of the additive in the salt bath within 4 h 29.5 ppm / h 24.3 ppm / h 35.2 ppm / h 26.3 ppm / h 31.3 ppm / h 26.7 ppm / h 28.9 ppm / h 18.7 ppm / h Iron ion concentration after 15 h of purification 1.5 ppm 2.3 ppm 1.2 ppm 2.5 ppm 1.3 ppm 2.7 ppm 2.9 ppm 3.4 ppm The above impurity removal experiments 1 to 8 fully demonstrate that the salt bath purification additive material can quickly absorb the iron ions generated in the salt bath during the chemical strengthening process. The absorption efficiency within the first four hours is very high, with a minimum of 18.7 ppm / h. Compared with the existing technology, this greatly improves the iron ion purification efficiency of the salt bath, which is conducive to improving overall production capacity.

[0038] Example 7 First, the additive was prepared and characterized. 35wt% SiO2, 25wt% Al2O3, 37wt% Na2O, and 3wt% P2O5 were thoroughly mixed. The additive raw materials were preheated to 300-400°C, then melted at 900-1400°C to form a liquid. The molten glass was then rolled into a sheet of additive using rollers. The resulting additive composition was 35wt% SiO2, 25wt% Al2O3, 37wt% Na2O, and 3wt% P2O5. The XRD pattern of the prepared additive is shown below. Figure 6 As shown by Figure 6 It can be seen that the additive at this time is amorphous.

[0039] Next, the prepared additive is put into the furnace for use. Weigh 1wt% of the additive in the glass strengthening salt bath containing lithium ions, add it to the glass strengthening salt bath containing lithium ions, and react at 480℃ for 4 hours. Observe the appearance of the additive. If it is transparent, it means that the reaction is not complete and can be used again. If it is opaque white, it means that it is complete. XRD test is performed on the additive after sintering. The test results are as follows: Figure 7 As shown by Figure 7 It can be seen that no changes have occurred, just like before the furnace was put into use.

[0040] Examples 8-12 The overall preparation method and application method are the same as those in Example 7. The differences are the composition of the raw materials, the form of the additive, the temperature in the furnace when it is put into use (to remove impurities), and the amount of input, etc., as shown in Tables 7 and 8.

[0041] Table 7 Raw material composition and morphology of Examples 7-11 Example SiO2(wt%) Al2O3 (wt%) Alkali metal oxide (wt%) Other metal oxide (wt%) Example 7 35 25 Na2O 37 P2O53 Example 8 38 22.5 Na2O 36 P2O53.5 Example 9 41 20 Na2O 35, K2O 2 P2O52 Example 10 38 24 Na2O 33, K2O 1 MgO 4 Example 11 36 21 Na20 38, K20 0.5 MgO 4.5 The flaky additives obtained in Examples 7-11 were tested for lithium ion removal. The test results are shown in Table 8.

[0042] Table 8 Comparative table of the effects of removing lithium ions from glass strengthening salt baths in Examples 7-11 Decontamination experiment 9 Decontamination experiment 10 Decontamination experiment 11 Decontamination experiment 12 Decontamination experiment 13 Additive Example 7 Example 8 Example 9 Example 10 Example 11 Lithium ion concentration in the salt bath 200 ppm 200 ppm 200 ppm 200 ppm 200 ppm Salt bath temperature 480℃ 480℃ 500℃ 500℃ 530℃ Additive usage amount 1 wt% of the mass of the salt bath 1 wt% of the mass of the salt bath 1 wt% of the mass of the salt bath 2 wt% of the mass of the salt bath 2 wt% of the mass of the salt bath Reaction time of the additive in the salt bath 4h 5h 6h 4h 8h Lithium ion concentration in the salt bath after lithium reduction 140 ppm 110 ppm 105 ppm 70 ppm 38 ppm Appearance of the additive after use Mainly white opaque, with a small amount of transparent (insufficient reaction) White opaque White opaque Mainly white opaque, with a large amount of transparent (can be reused) White opaque The additive prepared in Example 8 was subjected to lithium removal experiment, and then was sintered under the same sintering conditions as in Example 7, and then was subjected to XRD test, and the results are shown in Table 1. Figure 8 As shown in Table 1, the additive after being used in the furnace began to produce sodium aluminum silicon crystals, and the crystallinity was ≥80%.

[0043] Experiments 9-11 can show that the additive of the present application can effectively control the lithium ion concentration by absorbing the additive under the existing strengthening mode of production, and the use state of the additive can be quickly confirmed according to the appearance, thereby saving the additive and reducing the production cost. Today, in a glass processing factory, the size of the strengthening furnace used can be 1000 to 10000 pieces of glass products at a time, if the molten salt cannot be effectively controlled, resulting in product defects, it will be a great waste of cost, and with the increase of the input batch, the quality control between batches is also very important.

[0044] The present application can quickly confirm the required additive mass according to the amount of glass input (the amount of lithium ions exchanged), to maintain the stability of the lithium ion concentration in the molten salt. At the same time, the additive can be put into the furnace together with the glass, and the lithium reduction operation is carried out while the ion exchange of the glass is carried out, to realize the online monitoring and rapid lithium reduction scheme, to ensure the stability of glass strengthening between different batches, and to reduce the production cost.

Claims

1. A method for removing impurities from a glass strengthening salt bath, characterized in that: The additive is prepared from 20-60% SiO2, 10%-40% Al2O3, 20-50% of a first metal oxide, and 0-30% of other oxides in percentage by mass. 1-2% of the mass of the glass-strengthening salt to be removed is weighed and added to the glass-strengthening salt to be removed. The mixture is reacted at 460-500°C for 3-20 hours to remove iron ions from the glass-strengthening salt bath.

2. The method for removing impurities from a glass strengthening salt bath according to claim 1, wherein: The first metal oxide is Li2O, Na2O, K2O, R b2 O; the other oxides are one or more of P2O5, CaO, MgO, BaO, SrO, AgO, ZrO2, Sb2O3, ZnO, B2O3, Fe2O3, NiO, and TiO2.

3. The method for removing impurities from a glass strengthening salt bath according to claim 1 or 2, characterized in that: The additive is in the form of particles, flakes or porous particles.

4. The method for removing impurities from a glass strengthening salt bath according to claim 3, wherein: When the additive is in the form of particles, the average size thereof is 1-20 mm; when the additive is in the form of flakes, the thickness thereof is 0.3-1.2 mm; when the additive is in the form of porous particles, the average pore size thereof is 1-10 mm.

5. The method for removing impurities from a glass strengthening salt bath according to claim 1, wherein: The preparation method of the additive is: fully mix 20-60wt% SiO2, 10-40wt% Al2O3, 20-50wt% alkali metal oxide and 0-30wt% other oxides, melt the mixture between 900℃ and 1600℃ to form a liquid state, and then make it into granular, flake or porous shapes.

6. The method for removing impurities from a glass strengthening salt bath according to claim 5, wherein: The liquid mixture is granulated by water quenching at a temperature of 5-85°C.

7. The method for removing impurities from a glass strengthening salt bath according to claim 5, wherein: The liquid mixture is prepared into a sheet by calendaring or drawing.

8. The method for removing impurities from a glass strengthening salt bath according to claim 5, wherein: The liquid mixture is made into a porous shape by adding a foaming agent, wherein the foaming agent is carbon powder and / or sodium carbonate.

9. A method for removing impurities from a glass strengthening salt bath, characterized in that: The additive is made of 30-55% SiO2, 5%-30% Al2O3, 35-55% of a first metal oxide and 1-6% of other oxides in mass percentage. 1-2% of the mass of the glass-reinforced salt to be removed is weighed and added to the glass-reinforced salt to be removed. The additive is added to the glass-reinforced salt to be removed at 450-550°C for a reaction time of 4-16 hours to remove lithium ions from the glass-reinforced salt bath.

Citation Information

Cited By

  • Sodium ion adsorbent as well as preparation method and application thereof

    CN121550954A